As transformações nas concepções de controle da Petrobras: 1997 A 2022 - Dias, Marcos Roberto (Universidade Federal de São Carlos, 2024)
This research investigates the transformations in the conceptions of control at Petrobras between 1997 and 2022. The concept of conception of control was developed by Neil Fligstein and is defined as totalizing worldviews that bias the perception of senior managers in organizations, guiding the forms of internal coordination and prevailing business strategies. These conceptions arise from internal power relations between organizational subunits and the professional profile of the individuals who concentrate power in the organization, which are decisively influenced by the relationship of the organization with its organizational field and with the State. In recent decades, a context of increasing financialization of global economies has driven the so-called conception of control of shareholder value. The work seeks to evaluate how this process has occurred at Petrobras, a mixed-capital company that is among the most important in Brazil. To this end, a qualitative and historical research is carried out seeking to understand the main transformations that the company has undergone since its IPO. The changes in corporate governance, the profile of managers and business strategies are investigated based on secondary data collected from the company's institutional documents and other sources. The analysis reveals that the company's capitalization via the market has gradually driven the implementation of the concept of shareholder value. This business model competes for hegemony with the concept of control associated with manufacturing, on the basis of which the company emerged and consolidated itself. While the advancement of the concept of shareholder value has permeated governments from different positions on the political spectrum, it is clear that right-wing governments have been decisive in advancing this process. The corruption scandals that the company has been through were leveraged by minority shareholders, triggering reforms in its corporate governance that served to expand its influence on management.
The transformations in the conceptions of control at Petrobras between: 1997 and 2022
Keywords: Concepções de controle; Governança corporativa; Financeirização; Petrobras; Concepts of control; Corporate governance; Financialization; Petrobras; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA